Barriers to fire spread in northern Australian tropical savannas, deriving fire edge metrics from long term high-frequency fire histories. (1st January 2022) - Fisher, Rohan; Lewis, Ben; Price, Owen; Pickford, Anna
Abstract: The savannas of northern Australia are amongst the most fire-prone landscapes in the world. However, over the last fifteen years, increasing effort has been put into reducing fire extent and severity using prescribed burning strategies early in the dry season. This study seeks to improve the application of strategic fire management by providing a more detailed understanding of the landscape features that impede fire spread in Australia's tropical savannas using long-term satellite-derived fire histories. Spatial analysis of fire edges in Kakadu National Park based on fine-scale (30 m) Landsat imagery found that most fires stopped along linear edges, which were primarily associated with known features (roads, rivers and cliffs). Further analysis found linear features with the highest stopping ability covered only 13% of the park but divided the whole park into smaller containment regions. The stopping power of each feature type was found to vary according to their width and to change during the fire season, results that could help plan strategic fuel reduction burns. Similar results were seen with the lower-resolution continental-scale MODIS satellite-derived edge data. The MODIS dataset provided a means for applying fire edge analysis to support planning in areas of northern Australia that lack fine scale fire history mapping. Highlights: The high fire frequency in northern Australia allowed fire extinction analysis. An analysis of fire edges was conducted using satellite-derived fire data. We have produced a spatially explicit map of fire stopping probability. These data can support a more strategic approach to prescribed burns.